Surgery lengthens survival for collecting duct carcinoma: analysis of hospital-based cancer registry data in Japan - Shuya Kandori; Shuhei Suzuki; Kosuke Kojo; Bunpei Isoda; Takazo Tanaka; Satoshi Nitta; Masanobu Shiga; Yoshiyuki Nagumo; Atsushi Ikeda; Takashi Kawahara; Akio Hoshi; Hiromitsu Negoro; et al. (BMC Cancer)
Abstract Background To identify the prognosis of Japanese patients with collecting duct carcinoma (CDC). Methods We used a hospital-based cancer registry data in Japan to extract CDC cases that were diagnosed in 2013, histologically confirmed, and determined the first course of treatment. We further investigated treatment modalities and estimated overall survival (OS) by the Kaplan–Meier method. Results A total of 61 CDC patients were identified. The 5-year OS rate for all CDC patients who were diagnosed in Japan during 2013 was 23.6% (95% CI: 15.0–37.4), with a median OS of 14 months (95% CI: 12–24). The 5-year OS rate for CDC patients at stages I, III, and IV were 53.0% (95% CI: 29.9–94.0), 35.7% (95% CI: 19.8–64.4), and 3.4% (95% CI: 0.5–23.7), respectively. Noteworthy, the 1-year OS for stage IV patients was 27.6% (95% CI: 0.5–23.7) and the median OS was only 5 months (95% CI: 4–12). We further examined the OS for advanced disease according to treatment modalities. The median OS of patients who undertook chemotherapy alone was significantly shorter than patients who undertook surgery alone for advanced disease (4 months [95% CI: 4-NA] vs. 15 months [95% CI: 13–68]; p < 0.001) and surgery-only patients had a similar median OS as surgery-plus-chemotherapy patients (19 months [95% CI: 13-NA]; p < 0.001). Moreover, a multivariable analysis for the OS in advanced disease revealed that surgery-plus-chemotherapy patients had significantly more favorable prognoses (HR 0.21, 95% CI: 0.07–0.57). Conclusions Japanese CDC patients face poor prognoses similar to Western countries, especially in advanced cases that receive only chemotherapy. Surgery appears necessary for advanced disease.